2006
DOI: 10.1002/app.25098
|View full text |Cite
|
Sign up to set email alerts
|

Lignin‐based polycondensation resins for wood adhesives

Abstract: Lignin-based wood adhesives are obtained that satisfy the requirements of relevant international standards for the manufacture of exterior-grade wood particleboard. Formulations based on low molecular mass lignin and presenting an increase in the relative proportion of reactive points yield better results than the higher molecular mass lignin used in the past. These lignins allow a higher proportion of hydroxymethylation during preparation of methylolated lignins. These lignin-based adhesives also yield accept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
116
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(123 citation statements)
references
References 50 publications
3
116
0
4
Order By: Relevance
“…Based on the estimated elastic properties of adhesive coated strands, the homogenization procedure of Stürzenbecher et al (2010b) was applied, accounting for the compaction, the strand orientation distribution, the layer assembly and the density profile across the panel thickness. The elastic behavior of the tannin and the lignin adhesives in their cured state was assumed to be isotropic with a Poisson's ratio of 0.3 and a modulus of 1.8 GPa (Garcia and Pizzi 1998;Osman and Pizzi 2002) and 2.1 GPa (Mansouri et al 2007b), respectively. As the density profiles were not measured at every test specimen, one characteristic representative of all measured density profiles was taken for modeling of all panels.…”
Section: Modeling the Elastic Properties Of The Panelsmentioning
confidence: 99%
“…Based on the estimated elastic properties of adhesive coated strands, the homogenization procedure of Stürzenbecher et al (2010b) was applied, accounting for the compaction, the strand orientation distribution, the layer assembly and the density profile across the panel thickness. The elastic behavior of the tannin and the lignin adhesives in their cured state was assumed to be isotropic with a Poisson's ratio of 0.3 and a modulus of 1.8 GPa (Garcia and Pizzi 1998;Osman and Pizzi 2002) and 2.1 GPa (Mansouri et al 2007b), respectively. As the density profiles were not measured at every test specimen, one characteristic representative of all measured density profiles was taken for modeling of all panels.…”
Section: Modeling the Elastic Properties Of The Panelsmentioning
confidence: 99%
“…Lignin is polyphenolic and contains an unsubstituted carbon at either the C3 or C5 position on the aromatic ring. It also contains free phenolic and aliphatic hydroxyl groups that can form a quinone methide intermediate, which reacts with an aldehyde, tannin, phenol, or isocyanate group with heating under alkaline conditions (Ballerini et al 2005;El Mansouri 2007a;Abdelwahab and Nassar 2011;Mansouri et al 2011). Due to these chemical characteristics, lignin is a good starting material for wood adhesives (Cetin and Ozmen 2002;Cavdar et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Particleboard containing 10% of adhesive was fabricated with two formulations, which consisted of 55/20/25 glyoxalated calcium lignosulfonate/pMDI/PF proportions and 60/40 glyoxalated calcium lignosulfonate/pMDI proportions (El Mansouri et al 2007a). It was found that IB strengths of the particleboard bonded with these adhesives met the minimum requirement as stipulated in EN 312 1995.…”
Section: Introductionmentioning
confidence: 99%
“…These materials are considered to be environmentally friendly due to the fact that they incorporate lignocellulosic biomass, which is a renewable resource, as a raw material. Usually, synthetic resin adhesives derived from fossil resources are used in wood-based materials to obtain satisfactory bond performance (Yang et al 2006;Mansouri et al 2007;Krug 2010;Hoong et al 2011). However, as the shortage of fossil resources and the deterioration of global environment have been serious problems, it is necessary to develop renewable resources instead of fossil resources.…”
Section: Introductionmentioning
confidence: 99%